The Johan Bergh Historia Award (Historia, 2021)
The Historical Association of South Africa (HASA) invites Heads of Department to nominate their top third year student for the Johan Bergh Historia Award. This award is in recognition of Prof Johan Bergh, who was president of HASA for over two decades, and is in line with his on-going commitment to promote History at postgraduate level. The winners will receive a year’s subscription to Historia and their names will be announced in the first issue of Historia in the subsequent year.
Keywords: The Johan Bergh Historia Award